2006
DOI: 10.1051/agro:2006014
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus fertilizers as a source of uranium in Serbian soils

Abstract: Around 1500 t of mineral fertilizers based on phosphorus are applied per annum in Serbia. It is estimated that around 210 kg of uranium (30 g/ha) are in this way introduced into the environment. Due to this fact there is a risk of exposing local population to ionizing radiation. The purpose of this article was to determine whether long-term application of phosphorus fertilizers causes increase of uranium content in arable soils. These investigations were made using field experiments that were set up on three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 4 publications
3
13
0
2
Order By: Relevance
“…Long-term application of phosphate fertilizers identified increase uranium content in treated soil. Physicochemical soil properties have an effect on the process of uranium migration and mobilization (Rothbaum et al 1979;Stojanović et al 2006a;Stojanović 2006b;Guzmá n et al 2006;Ghosh et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Long-term application of phosphate fertilizers identified increase uranium content in treated soil. Physicochemical soil properties have an effect on the process of uranium migration and mobilization (Rothbaum et al 1979;Stojanović et al 2006a;Stojanović 2006b;Guzmá n et al 2006;Ghosh et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Kontaminacija životne sredine teškim metalima i radionuklidima dovodi do narušavanja prirodnih geohemijskih ciklusa i ravnoteže ekosistema [ Široka upotreba nuklearne energije, primena oružja sa osiromašenim uranijumom, nuklearna testiranja, sagorevanje uglјa, proizvodnja nafte i gasa, prerada fosfatnih ruda, proizvodnja i primena fosfornih đubriva lošeg kvaliteta, nebezbedna jalovišta prerade uranijumskih ruda su glavni antropogeni izvori uranijuma u životnoj sredini [4][5][6]. Sve navedene lјudske aktivnosti doprinose Tehnološki uslovljenoj povišenoj prirodnoj radioaktivnosti, tj.…”
Section: Uvodunclassified
“…In addition to the natural variation, human activities can affect the distributions of U, Th and K. Within the last 10 years, there has been increased interest amongst scientists concerning the application of mainly U through fertiliser addition (Agbenin and Felix-Henningsen, 2001;Ahmed and El-Arabi, 2005;Becegato et al, 2008b;Guzman et al, 2006;Stojanovic et al, 2006;Takeda et al, 2006;Tunney et al, 2009). Chemical (phosphorus) P fertilisers are derived from processed rocks that contain high amounts of phosphate minerals (Cevik et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The reported accumulation of U in the topsoil from long-term P fertiliser additions ranges from 0.08 to 0.63 mg kg − 1 (Rothbaum et al, 1979;Stojanovic et al, 2006;Takeda et al, 2006;Tunney et al, 2009;Yamaguchi et al, 2009). Few studies assess Th, but Becegato et al (2008b) reported increases in Th of 0.1 Bq kg − 1 in sandy-clayey soils and increases of 2.8 Bq kg − 1 in clayey soils in an intensively cultivated area compared to a native forest in Brazil.…”
Section: Introductionmentioning
confidence: 99%